2022
DOI: 10.1088/1361-6560/ac508c
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of kV mini-GRID spatially fractionated radiation therapy: dosimetry and preclinical trial

Abstract: Objective: To develop and characterize novel methods of extreme spatially fractionated kV radiation therapy (including mini-GRID therapy) and to evaluate efficacy in the context of a pre-clinical mouse study. Approach: Spatially fractionated GRIDs were precision-milled from 3 mm thick lead sheets compatible with mounting on a 225 kVp small animal irradiator (X-Rad). Three pencil-beam GRIDs created arrays of 1 mm diameter beams, and three ‘bar’ GRIDs created 1x20 mm rectangular fields. GRIDs projected 20x20 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…Although slightly different X‐ray beams were used for irradiation, the trends of an increasing valley dose and decreasing peak dose, as well as the resulting steadily decreasing PVDR are similar. Additionally, the findings of increasing FWHM and ctc with increasing depth agree with previous studies, where the same trend was observed 26 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although slightly different X‐ray beams were used for irradiation, the trends of an increasing valley dose and decreasing peak dose, as well as the resulting steadily decreasing PVDR are similar. Additionally, the findings of increasing FWHM and ctc with increasing depth agree with previous studies, where the same trend was observed 26 …”
Section: Discussionsupporting
confidence: 92%
“…When comparing the behavior of dose as a function of depth for the peak and valley doses (Figure 5), the obtained results are in agreement with previous publications. 9,16,25,26 Although slightly different X-ray beams were used for irradiation, the trends of an increasing valley dose and decreasing peak dose, as well as the resulting steadily decreasing PVDR are similar. Additionally, the findings of increasing FWHM and ctc with increasing depth agree with previous studies, where the same trend was observed.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The output factor in this study is comparable to those in the work by Johnson et al (2022), although slightly larger due to the larger hole radii employed in our grid design. The PVDR, which mainly depends on the open area ratio in an inverse relationship, is larger in our grid configuration compared to their 2 mm spacing grid.…”
Section: Discussionsupporting
confidence: 79%
“…Grid therapy operates on radiobiological principles that exploit the spatial fractionation of radiation to minimise the irradiated volume of normal tissue, enabling unirradiated cells to migrate into damaged regions. Although the tumour volume also experiences reduced irradiation, the effectiveness of grid therapy persists due to non-targeted effects and other radiobiological factors such as bystander effects, alterations in tumour vasculature, and immune responses (Moghaddasi et al 2022) In a previous study by Johnson et al (2022), physical attenuating grids were developed for use in a preclinical beam setting. These mini-grids were made of lead and featured non-diverging hexagonal array cylindrical holes.…”
Section: Introductionmentioning
confidence: 99%